Implementation of the company's CSR program for SMEs: Will the program effectiveness increase the company’s awareness? - Phima Ruthia Dwikesumasari; Verina Veda Faidhatul Markumah (Universitas Pendidikan Nasional, 2021)
Firms wield considerable influence over development as well as their contribution to regional economies, job creation, and business development. Their contribution to development can be understood from the perspective of the Corporate Social Responsibility (CSR) program. The impact of firms’ CSR initiatives and brand awareness of the organization is a critical issue that needs to be addressed. Company X is one of the service firms engaged in business consulting. Company X's primary CSR program is CSR Program A, which focuses on empowering SMEs in Surabaya, Indonesia, to excel in their respective industries. The researcher employed a qualitative approach in this study, conducting interviews with five informants to elicit information regarding a company's CSR program for SMEs. The results were: (1) the CSR programs implemented were effective and met the demands of SMEs. The company's commitment to optimizing the implementation of this program's action plan will boost program members' loyalty; and (2) initially, SMEs owners were unaware of the CSR program provider businesses in which they participated. However, while implementing the program, the corporation provided mentors and presenters throughout the course of the program. In turn, resulting in the gradual formation of the second level of company consciousness. Additionally, the presence of a comprehensive CSR program action plan enhances the program's effectiveness from the perspective of program participants, ensuring that CSR programs are associated with a favorable company image (top level of awareness). Future research can expand this analysis by conducting quantitative research to boost the generalizability of the research findings. Prepositions can be used to construct hypotheses.